Динаміка видового складу й вікова структура деревних насаджень лісового ландшафтного району дендропарку “Тростянець” - Ilyenko, A.A.; Medvedev, V.A. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2010)
The changes in species composition and abundance of introductive and local species of woody plants of forest landscape area of dendropark Trostyanets, that have occurred over the past 50 years are analyzed. The results of studying the age structure of planting are presented. The appropriateness of the reconstruction of the forest landscape is justified.